Ultraviolet activation enhanced composite gas sensor after vacuum annealing and preparation method thereof

Through vacuum annealing and ultraviolet excitation technology, the sensitivity and selectivity of gas sensors are improved, and the shortcomings of existing sensors in terms of anti-interference ability, life, restrictions and costs are solved, and efficient and economical gas monitoring is achieved.

CN119510514AActive Publication Date: 2025-02-25TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411616352.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-25
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

Existing gas sensors have shortcomings in anti-interference capabilities, lifespan, restrictions and costs, making it difficult to achieve high-precision, stable and economical gas monitoring in complex environments.

Method used

The composite gas sensor with enhanced ultraviolet activation after vacuum annealing is used to optimize the electronic structure of the material surface through vacuum annealing, and the activity of gas molecules is improved by using ultraviolet light excitation, thereby improving the sensitivity and selectivity of the sensor.

Benefits of technology

It realizes high sensitivity, selectivity and fast response gas detection, reduces operating temperature, improves anti-interference ability, reduces costs, and expands application areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119510514A_ABST
    Figure CN119510514A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of gas sensors, in particular to an ultraviolet activation enhanced composite gas sensor after vacuum annealing and a preparation method thereof, and the preparation method comprises the following steps: step 1, preparing a sensitive material; step 2, preparing the gas sensitive element; 3, setting a light source; step 4, performance testing; and step 5, data analysis. According to the invention, the sensitivity and selectivity of gas detection, especially detection of carbon dioxide gas, can be better improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of gas sensors, in particular to a composite gas sensor enhanced by ultraviolet activation after vacuum annealing and a preparation method thereof. Background Art

[0002] With the global attention paid to climate change and environmental issues, the monitoring of carbon dioxide (CO2) emissions has become particularly important. As one of the key technologies for monitoring air quality, carbon dioxide sensors are widely used in environmental protection, medical, agricultural, industrial and other fields. In the field of carbon dioxide sensor research, researchers around the world have developed a variety of high-precision detection technologies, including colorimetric fluorescence, surface plasmon resonance (SPR), surface acoustic wave (SAW) and microcantilever sensors. Colorimetric fluorescence sensors, based on their light absorption and emission principles, have extremely high sensitivity to small changes in refractive index, but they have deficiencies in gas selectivity, reliability and anti-pollution ability, which limits their application in a wider range of environments. Surface plasmon resonance sensors have attracted attention for their extremely low detection limits and label-free detection, but there are challenges in gas selectivity and multi-platform compatibility, which restricts their application in large-scale research. Surface acoustic wave and microcantilever CO2 sensors show extraordinary detection limits, but there is a lack of sufficient research and reports on key parameters such as gas selectivity, stability and response / recovery time. In addition, non-dispersive infrared spectroscopy (NDIR) uses the unique optical fingerprint of CO2 gas and is well suited for detecting lower concentrations of CO2, but may encounter cross-sensitivity issues in the presence of interfering gases. Electrochemical methods have good gas selectivity and stability, but their deployment in a wider range of applications is limited by complex component configurations, high operating temperatures, and high operating costs. As a cost-effective and easily miniaturized technology, chemiresistor methods work on the principle of a reversible carbonization reaction achieved through charge transfer between metal oxides and chemically adsorbed CO2 molecules.

[0003] The existing technical solution is the ultraviolet differential absorption spectroscopy sensor (UV-DOAS), which is a sensor that uses ultraviolet absorption spectrum to analyze gas composition. Although the ultraviolet differential absorption spectroscopy sensor (UV-DOAS) has many advantages, it also has some disadvantages and limitations:

[0004] (1) Spectral overlap problem: When detecting multiple gases, the absorption spectra of the gases may overlap, which makes it difficult to accurately distinguish the concentrations of different gases. This spectral overlap is a major challenge of UV-DOAS technology, especially in complex gas mixtures.

[0005] (2) Noise interference: Due to the limitation of short optical path, the measurement process may be affected by noise, which will reduce the accuracy of concentration inversion. Noise interference may lead to unstable and inaccurate measurement results.

[0006] (3) Light source life: UV light sources have a limited lifespan and usually need to be replaced regularly to maintain sensor accuracy and stability. This increases maintenance costs and operational complexity.

[0007] (4) Environmental dependence: The performance of UV-DOAS sensors may be affected by environmental conditions (such as temperature, humidity, etc.), which may cause fluctuations in measurement results.

[0008] (5) Cost issue: Although UV-DOAS sensors have advantages in performance, their initial investment and maintenance costs are relatively high, which may limit their widespread use in certain applications.

[0009] (6) Response time: Although the response time of UV-DOAS sensors is relatively fast, it may still be slower than other types of sensors in some cases, which may be a disadvantage in applications that require real-time monitoring. Summary of the invention

[0010] The present invention provides a composite gas sensor enhanced by ultraviolet activation after vacuum annealing and a preparation method thereof, which can overcome the deficiencies of existing sensors in terms of anti-interference ability, lifespan, limiting conditions and cost.

[0011] The method for preparing the composite gas sensor enhanced by ultraviolet activation after vacuum annealing according to the present invention comprises the following steps:

[0012] Step 1: Preparation of sensitive materials;

[0013] Step 2, preparation of gas sensing element;

[0014] Step 3: Set the light source;

[0015] Step 4: Performance test;

[0016] Step 5: Data analysis.

[0017] Preferably, in step 1, specifically:

[0018] 1.1) Dissolve La(NO3)3·6H2O, Fe(NO3)3·9H2O, Co(NO3)2·6H2O and citric acid in a molar ratio of 1:0.8:0.2 in deionized water according to a certain proportion, and stir with a magnetic stirrer until the chemical reagents are completely dissolved;

[0019] 1.2) The mixed solution was transferred to a reactor, reacted at 180°C for 9 hours, and the precipitate generated by the reaction was collected after natural cooling to room temperature, washed with anhydrous ethanol to obtain LFCO precursor precipitate, and dried at 60°C for 3 hours to remove water and organic matter;

[0020] 1.3) The dried precipitate was calcined in a tube furnace at 600°C for 2 h to obtain a sample LFCO, the sample LFCO was dissolved in deionized water, and nanopowders of Zn(NO3)2·6H2O and Co(NH2) in a molar ratio of 1:1 were added thereto, and the mixture was fully stirred using a magnetic stirrer;

[0021] 1.4) The fully mixed solution was transferred to the reactor again and reacted at 150° C. for 10 h. After repeating the above steps to obtain a dry precipitate, it was placed in a tubular furnace again and calcined at 500° C. for 3 h to obtain a LFCO-ZNO composite material.

[0022] Preferably, in step 1.1), the certain ratio is: (La 3+ +Fe 3+ +Co 2+ ):(citric acid)=1:2.

[0023] Preferably, in step 1.3), the sample LFCO is dissolved in deionized water, the solution concentration is 1 mmol / L, and the deionized water is 60 ml.

[0024] Preferably, in step 2, specifically:

[0025] 2.1) In an agate mortar, add appropriate amounts of LFCO-ZNO powder, propolis and glass fiber, then drop terpineol into the mixture and grind until a uniform and fine slurry is formed;

[0026] 2.2) Spray the slurry evenly on the surface of the ceramic tube to form a dense coating;

[0027] 2.3) The ceramic tube sprayed with LFCO-ZNO composite material is placed in a muffle furnace and sintered at a constant temperature of 200°C for 2 hours to achieve densification of the ceramic tube and complete the sensor D. LFCO-ZNO Production;

[0028] 2.4) Insert the nickel-chromium alloy heating wire into the ceramic tube and weld it to the base;

[0029] 2.5) After 24 hours of aging treatment, the production of the indirectly heated sintered sensor is completed.

[0030] Preferably, in step 2.1), the ratio of LFCO-ZNO powder, propolis, glass fiber and pinene alcohol is 10:1:1:2.

[0031] Preferably, in step 3, a low-power ultraviolet light emitting diode is used as an excitation light source when testing the gas sensitive element to form a light-excited gas sensor.

[0032] Preferably, in step 4, the gas-sensing performance of the gas-sensitive element is tested by an intelligent gas sensing analysis system; first, the intelligent gas sensing analysis system is turned on, the devices are placed in a test box in a certain order, the ultraviolet light is turned on, and a certain temperature is set in the range of 20°C-200°C, a certain amount of the gas to be tested is injected into the test box, and the gas is released after the resistance of the device is stable.

[0033] Preferably, in step 5, the experimental data is analyzed to evaluate the effect of ultraviolet light excitation on the performance of the gas sensor and determine the optimal working conditions.

[0034] The invention provides a composite gas sensor enhanced by ultraviolet activation after vacuum annealing, which is prepared by adopting the preparation method of the composite gas sensor enhanced by ultraviolet activation after vacuum annealing.

[0035] The sensor of the present invention has the following advantages:

[0036] A) High sensitivity, selectivity and fast response:

[0037] By using vacuum annealing and ultraviolet light excitation technology, the detection sensitivity and selectivity of specific gases (such as carbon dioxide) can be improved. Among them, vacuum annealing can change the electronic structure of the material surface, increase the adsorption sites on the material surface by removing surface impurities and defects, and thus optimize the electron transfer characteristics. Ultraviolet light excitation can provide high-energy photons, which can excite electrons on the surface of the material and increase the activity of electrons, thereby improving the sensor's response speed and sensitivity to gas molecules.

[0038] B) Low temperature operation:

[0039] Traditional metal oxide semiconductor (MOS) chemiresistor sensors need to be heated to a relatively high temperature (greater than 200°C) to achieve sensing functions. However, this sensor, through material design and photoexcitation technology, can operate at high performance at 100°C, reducing energy consumption and improving safety.

[0040] C) Strong anti-interference ability:

[0041] By optimizing the sensor material and design, the cross sensitivity to other gases can be reduced and the selectivity for the target gas (carbon dioxide) can be improved.

[0042] D) Low cost and easy integration:

[0043] The sensor is designed for cost-effectiveness and easy integration into existing systems.

[0044] E) High stability and repeatability:

[0045] The sensor is designed with long-term stability and repeatability in mind, which is critical to ensuring the sensor can provide reliable data under varying environmental conditions.

[0046] F)Multi-field application:

[0047] The technical effects of the new sensor give it important application potential in many fields such as environmental monitoring, industrial production, life medicine, etc., especially in the fields of greenhouse gas monitoring and energy conservation and emission reduction.

[0048] In summary, the technical effects of developing this new type of gas sensor are mainly focused on improving sensitivity, selectivity, reducing operating temperature, fast response, anti-interference ability, cost-effectiveness and wide application potential. These advances help to achieve efficient monitoring of key gases such as carbon dioxide, which is of great significance for environmental protection and industrial safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 It is a flow chart of a method for preparing a composite gas sensor enhanced by ultraviolet activation after vacuum annealing in an embodiment;

[0050] Figure 2 Schematic diagram of the X-ray diffraction pattern of LFCO-ZnO in the embodiment;

[0051] Figure 3 The SEM and EDS images of LFCO-ZnO in the embodiment;

[0052] Figure 4 This is a test diagram of the LFCO-ZNO nanosensor in the embodiment under ultraviolet light irradiation;

[0053] Figure 5 The resistance variation curve of the LFCO-ZNO nanosensor in the embodiment and the corresponding activation energy diagram;

[0054] Figure 6 Device D in the embodiment LFCO-ZNO Schematic diagram of the response to 500ppm CO2 gas as the operating temperature changes;

[0055] Figure 7 Schematic diagram of the dynamic response of the LFCO-ZNO nanosensor to 500 ppm CO2 in the embodiment. DETAILED DESCRIPTION

[0056] In order to further understand the content of the present invention, the present invention is described in detail in conjunction with the accompanying drawings and embodiments. It should be understood that the embodiments are only for explaining the present invention and are not intended to limit it.

[0057] Example

[0058] like Figure 1 As shown, this embodiment provides a method for preparing a composite gas sensor enhanced by ultraviolet activation after vacuum annealing, and its experimental purpose is:

[0059] A new type of vacuum annealing and light excitation composite gas sensor was developed, which used vacuum annealing and ultraviolet light excitation to improve the sensitivity and selectivity of gas detection and achieve high-sensitivity detection of concentrated carbon dioxide gas.

[0060] Experimental materials and instruments:

[0061] Experimental drugs: lanthanum nitrate (La(NO3)3·6H2O), iron nitrate (Fe(NO3)3·9H2O), cobalt nitrate (Co(NO3)3·6H2O), citric acid (C6H8O7), zinc nitrate (Zn(NO3)2·6H2O), urea (Co(NH2)), pineneol (C 10 H 18 O), propolis, fiberglass.

[0062] Tube furnace (vacuum annealing).

[0063] Ultraviolet light emitting diode (UV-LED) was used as the excitation light source.

[0064] Gas sensor substrates and electrode materials.

[0065] Gases required for the experiment, such as carbon dioxide (CO2), etc.

[0066] Experimental steps:

[0067] Step 1: Preparation of sensitive materials;

[0068] Specifically:

[0069] 1.1) La(NO3)3·6H2O, Fe(NO3)3·9H2O, Co(NO3)2·6H2O and citric acid in a molar ratio of 1:0.8:0.2 are dissolved in deionized water in a certain proportion, and stirred with a magnetic stirrer until the chemical reagents are completely dissolved; the certain proportion is: (La 3+ +Fe 3+ +Co 2+ ):(citric acid)=1:2;

[0070] 1.2) The mixed solution was transferred to a reactor, reacted at 180°C for 9 hours, and the precipitate generated by the reaction was collected after natural cooling to room temperature, washed with anhydrous ethanol to obtain LFCO precursor precipitate, and dried at 60°C for 3 hours to remove water and organic matter;

[0071] 1.3) The dried precipitate was calcined at 600°C for 2 h in a tube furnace to obtain a sample LFCO, the sample LFCO was dissolved in deionized water (the solution concentration was 1 mmol / L, and the deionized water was 60 ml), and nanopowders of Zn(NO3)2·6H2O and Co(NH2) in a molar ratio of 1:1 were added thereto, and the mixture was fully stirred using a magnetic stirrer;

[0072] 1.4) The fully mixed solution was transferred to the reactor again and reacted at 150°C for 10 h. After repeating the above steps to obtain a dry precipitate, it was placed in a tube furnace again and calcined at 500°C for 3 h to obtain LFCO-ZNO (LaFe 0.8 Co 0.2 O3-ZnO) composite materials.

[0073] Step 2, preparation of gas sensing element;

[0074] Specifically:

[0075] 2.1) In an agate mortar, add appropriate amounts of LFCO-ZNO powder, propolis and glass fiber, then drop terpineol in and grind until a uniform and fine slurry is formed; the ratio of LFCO-ZNO powder, propolis, glass fiber and terpineol is 10:1:1:2; the amount of terpineol needs to make the powder form a uniform slurry and maintain a moderate humidity, neither too dry nor too wet;

[0076] 2.2) Spray the slurry evenly on the surface of the ceramic tube to form a dense coating;

[0077] 2.3) The ceramic tube sprayed with LFCO-ZNO composite material is placed in a muffle furnace and sintered at a constant temperature of 200°C for 2 hours to achieve densification of the ceramic tube and complete the sensor D. LFCO-ZNO Production;

[0078] 2.4) Insert the nickel-chromium alloy heating wire into the ceramic tube and weld it to the base;

[0079] 2.5) After 24 hours of aging treatment, the production of the indirectly heated sintered sensor is completed.

[0080] Step 3: Set the light source;

[0081] When testing gas-sensitive elements, low-power ultraviolet light-emitting diodes are used as excitation light sources to form light-excited gas sensors.

[0082] Step 4: Performance test;

[0083] The gas-sensing performance of the gas sensor is tested by the intelligent gas sensing analysis system; first, the intelligent gas sensing analysis system (CGS-8, Beijing Elite Technology Co., Ltd.) is turned on, the devices are placed in the test box in a certain order, the ultraviolet light is turned on, and a certain temperature (range 20℃-200℃) is set to inject a certain amount of the gas to be tested into the test box, and the gas is released after the resistance of the device is stable.

[0084] Step 5: Data analysis;

[0085] Analyze experimental data, evaluate the effect of UV light excitation on gas sensor performance, and determine the optimal operating conditions.

[0086] Experiment time

[0087] The specific time of the experiment depends on the scale and complexity of the experiment, but it usually includes the preparation of sensitive materials (1-2 days), the fabrication and testing of devices (1-2 days), and data analysis and optimization (1-2 days). Therefore, the entire experiment may take about a week to complete.

[0088] This embodiment provides a composite gas sensor enhanced by ultraviolet activation after vacuum annealing, which is prepared by the above-mentioned method for preparing a composite gas sensor enhanced by ultraviolet activation after vacuum annealing.

[0089] The sensor provided in this embodiment has the following characteristics:

[0090] a) Enhanced anti-interference ability: Through carefully selected materials and structural design, the sensor can effectively resist the interference of other non-target gases in the environment and provide more accurate gas detection results.

[0091] b) Simplified operation process: The sensor design takes into account the user's convenience of operation and implements simplified operation steps, so that non-professionals can easily perform gas detection.

[0092] c) Reduced production costs: Optimizations have been made in material selection and production processes to reduce the production cost of the sensor, making it more competitive in the market.

[0093] d) Improved sensitivity: To address the problem of low sensitivity of traditional electrochemical sensors, the present invention draws on the technology of ultraviolet irradiation in UV-DOAS sensors to enhance the activity of gas molecules through ultraviolet irradiation, thereby improving the sensitivity of the sensor.

[0094] e) Application of vacuum annealing process: Combined with the vacuum annealing process, this process can improve the crystallinity and stability of the material, further improving the performance of the sensor.

[0095] f) Meeting environmental monitoring needs: This combined technology gives the sensor broader application prospects in environmental monitoring and carbon emission control, and can meet the growing demand for environmental monitoring.

[0096] Through these features, the gas sensor of the present invention has significantly improved performance and can provide more reliable and accurate technical support for environmental monitoring and industrial process control.

[0097] The specific test of gas sensors is as follows:

[0098] In the experiment, the CGS-8 intelligent gas-sensitive analysis system was used to accurately test the CO2 sensitivity of the gas sensor. The following are the detailed steps of the experimental operation: First, the gas sensor to be tested is accurately inserted into the socket groove of the system gas box base in a specific order. Then, the evaporation and fan device are started to ensure the stability of the experimental environment, and then the gas box cover is closed. Next, turn on the computer power supply, finely adjust the heating current to the level required for the experiment, perform necessary preheating treatment on the gas sensor, and turn on the ultraviolet light-emitting diode on the side of the instrument. During this process, we also carry out data acquisition work. After obtaining a stable initial resistance value to be measured, a certain amount of target gas is accurately extracted using a microsampler. Then, the target gas is slowly and steadily injected into the gas box through the gas injection hole, and the change of material resistance in the target gas is closely observed. When the resistance value reaches a stable state again and lasts for a period of time, open the gas box and continue to observe the change of resistance value. When the resistance value returns to the initial resistance value and lasts for a period of time, stop data acquisition and save the relevant data obtained. During the entire experimental process, we must always maintain a rigorous and steady attitude to ensure the accuracy and reliability of the experimental results.

[0099] Results and data analysis

[0100] Material bulk structure characterization: Figure 2 The X-ray diffraction (XRD) pattern of the composite material LFCO-ZnO is given. The test results show that the characteristic peaks of the composite material are consistent with all the diffraction peaks in the standard card of the orthorhombic perovskite crystal phase LaFeO3 (PDF#75-0541) and the standard card of the hexagonal wurtzite structure ZnO (PDF#36-1451), and do not contain other impurity peaks and are not doped with other substances, which confirms that the prepared composite material has a high purity.

[0101] Material morphology and elemental analysis characterization: Figure 3Parts (ac) in the figure are scanning electron microscope (SEM) images of the sample (LFCO-ZnO). These images clearly show that the sample generally presents a regular spherical structure, and the surface is covered with ZnO nanosheets. This unique surface morphology greatly increases the specific surface area of ​​the material, thereby providing more adsorption sites and diffusion channels for gas molecules. In addition, the PN heterojunction structure formed between LFCO and ZnO also effectively promotes the transfer of carriers, thereby significantly improving the response speed and sensitivity of the sensor. Figure 3 The (dj) section provides the energy dispersive spectrometer (EDS) analysis results of the sample, confirming that ZnO has been successfully composited on LaFe 0.8 Co 0.2 O3 surface, this composite structure is of great significance for improving the gas sensing properties of the material.

[0102] Material performance test results and analysis: Figure 4 In the test experimental curve shown, the responsivity ratio Rg / Ra is greater than zero at all test temperatures, indicating that the sample LFCO-ZNO always maintains its responsiveness during the test. LFCO-ZNO The response peak appears at 1700s, and the sensing temperature decreases slightly. This is because ultraviolet light irradiation can excite electrons in the material and generate electron-hole pairs. This excitation can replace traditional thermal excitation to realize gas detection, reduce operating temperature and energy consumption.

[0103] exist Figure 5 D LFCO-ZNO In the sensor test curve, the resistance value (R) decreases exponentially with the increase of temperature (T), which is consistent with the conductive mechanism of semiconductor materials. The relationship between the change of resistance (R) and temperature can be described by the following formula:

[0104]

[0105] Among them, R0 is the constant, Ea is the band gap energy (activation energy) of the semiconductor, k B is the Boltzmann constant, and T is the absolute temperature. As the temperature increases, the carrier concentration increases, resulting in a decrease in resistivity, which is consistent with the experimentally observed trend that resistance decreases with increasing temperature. Secondly, the conductivity of semiconductors is also related to the band gap energy. When the energy value is low, electrons can more easily overcome defect barriers and achieve the transition process. It is calculated that the activation energy of the device is only 0.34eV, so the sensitivity of the subsequent gas-sensitive response test is relatively high.

[0106] Figure 6 It shows that in the temperature range of 20℃ to 180℃, D LFCO-ZNOThe sensor's response to 500ppm CO2 gas. After data analysis, the sensor's response value was significantly improved, which shows that vacuum annealing and UV irradiation have a positive effect on improving the response value of the gas sensor.

[0107] from Figure 7 As can be seen, device D LFCO-ZNO It exhibits a short response recovery time, with the fastest response time reaching 2 seconds and the recovery time reaching 18 seconds, realizing the rapid adsorption and dissociation process of CO2.

[0108] In summary: LaFe was successfully prepared by hydrothermal method in this example. 0.8 Co 0.2 O3-ZnO composite nanomaterials, using the characteristics of PN heterostructure, significantly improve the gas-sensitive properties of CO2. Under ultraviolet light irradiation conditions, at an ambient temperature of 100°C, the material's response value to 500ppm CO2 gas is as high as 5.91, which is 5 times higher than the pure LaFeO3 sensor's response to 1000ppmCO2 gas at 300°C, which is 1.74. And compared with other previous studies, as shown in Table 1, this study significantly improves the sensitivity and response-recovery time to carbon dioxide gas.

[0109] Table 1 CO2 sensor performance comparison table

[0110]

[0111]

[0112] The present invention and its embodiments are described schematically above, and the description is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. Therefore, if a person skilled in the art is inspired by it and designs a structural method and an embodiment similar to the technical solution without creativity without departing from the purpose of the invention, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a composite gas sensor enhanced by ultraviolet activation after vacuum annealing, characterized in that: The following steps are involved: Step 1: Preparation of sensitive materials; Step 2, preparation of gas sensing element; Step 3: Set the light source; Step 4: Performance test; Step 5: Data analysis.

2. The method for preparing the composite gas sensor enhanced by ultraviolet activation after vacuum annealing according to claim 1, characterized in that: In step 1, specifically: 1.1) Dissolve La(NO3)3·6H2O, Fe(NO3)3·9H2O, Co(NO3)2·6H2O and citric acid in a molar ratio of 1:0.8:0.2 in deionized water according to a certain proportion, and stir with a magnetic stirrer until the chemical reagents are completely dissolved; 1.2) The mixed solution was transferred to a reactor, reacted at 180°C for 9 hours, and the precipitate generated by the reaction was collected after natural cooling to room temperature, washed with anhydrous ethanol to obtain LFCO precursor precipitate, and dried at 60°C for 3 hours to remove water and organic matter; 1.3) The dried precipitate was calcined in a tube furnace at 600°C for 2 h to obtain a sample LFCO, the sample LFCO was dissolved in deionized water, and nanopowders of Zn(NO3)2·6H2O and Co(NH2) in a molar ratio of 1:1 were added thereto, and the mixture was fully stirred using a magnetic stirrer; 1.4) The fully mixed solution was transferred to the reactor again and reacted at 150° C. for 10 h. After repeating the above steps to obtain a dry precipitate, it was placed in a tubular furnace again and calcined at 500° C. for 3 h to obtain a LFCO-ZNO composite material.

3. The method for preparing the composite gas sensor enhanced by ultraviolet activation after vacuum annealing according to claim 2, characterized in that: In step 1.1), the certain ratio is: (La 3+ +Fe 3+ +Co 2+ ):(citric acid)=1:

2.

4. The method for preparing the composite gas sensor enhanced by ultraviolet activation after vacuum annealing according to claim 3, characterized in that: In step 1.3), the sample LFCO is dissolved in deionized water, the solution concentration is 1 mmol / L, and the deionized water is 60 ml.

5. The method for preparing the composite gas sensor enhanced by ultraviolet activation after vacuum annealing according to claim 4, characterized in that: In step 2, specifically: 2.1) In an agate mortar, add appropriate amounts of LFCO-ZNO powder, propolis and glass fiber, then drop terpineol into the mixture and grind until a uniform and fine slurry is formed; 2.2) Spray the slurry evenly on the surface of the ceramic tube to form a dense coating; 2.3) The ceramic tube sprayed with LFCO-ZNO composite material is placed in a muffle furnace and sintered at a constant temperature of 200°C for 2 hours to achieve densification of the ceramic tube and complete the sensor D. LFCO-ZNO Production; 2.4) Insert the nickel-chromium alloy heating wire into the ceramic tube and weld it to the base; 2.5) After 24 hours of aging treatment, the production of the indirectly heated sintered sensor is completed.

6. The method for preparing the composite gas sensor enhanced by ultraviolet activation after vacuum annealing according to claim 5, characterized in that: In step 2.1), the ratio of LFCO-ZNO powder, propolis, glass fiber and pinene alcohol is 10:1:1:

2.

7. The method for preparing the composite gas sensor enhanced by ultraviolet activation after vacuum annealing according to claim 6, characterized in that: In step 3, a low-power ultraviolet light emitting diode is used as an excitation light source when testing the gas sensitive element to form a light-excited gas sensor.

8. The method for preparing the composite gas sensor enhanced by ultraviolet activation after vacuum annealing according to claim 7, characterized in that: In step 4, the gas-sensing performance of the gas-sensitive element is tested by the intelligent gas sensing analysis system; first, the intelligent gas sensing analysis system is turned on, the devices are placed in a test box in a certain order, the ultraviolet light is turned on, and a certain temperature is set in the range of 20°C-200°C, a certain amount of the gas to be tested is injected into the test box, and the gas is released after the resistance of the device is stable.

9. The method for preparing the composite gas sensor enhanced by ultraviolet activation after vacuum annealing according to claim 8, characterized in that: In step 5, the experimental data is analyzed to evaluate the effect of UV light excitation on the performance of the gas sensor and determine the optimal working conditions.

10. A composite gas sensor enhanced by UV activation after vacuum annealing, characterized in that: The composite gas sensor is prepared by the method for preparing a composite gas sensor enhanced by ultraviolet activation after vacuum annealing as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • SmFeO3-based conductance acetone gas sensitive material, preparation method and application thereof

    CN101532976A

  • High gas response and selective LaFeO3-based ethanol gas sensor element and preparation method thereof

    CN108205002A

  • Preparation method of carbon dioxide gas sensor and prepared gas sensor

    CN115406944A